Measurement of the CP-violation parameter of B-0 mixing and decay with p(p)over-bar ->mu mu X data - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Agelou, M.; Aguilo, E.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; et al. (American Physical Soc, 2006)
We measure the dimuon charge asymmetry A in p (p) over bar collisions at a center of mass energy root s=1960 GeV. The data was recorded with the D0 detector and corresponds to an integrated luminosity of approximately 1.0 fb(-1). Assuming that the asymmetry A is due to asymmetric B-0 <->(B) over bar (0) mixing and decay, we extract the CP-violation parameter of B-0 mixing and decay: ((epsilon B0))/(1+vertical bar epsilon B0 vertical bar 2)=(AB0)/(4)= -0.0023 +/- 0.0011(stat)+/- 0.0008(syst).A(B)(0) is the dimuon charge asymmetry from decays of B-0(B) over bar (0) pairs. The general case, with CP violation in both B-0 and B-s(0) systems, is also considered. Finally we obtain the forward-backward asymmetry that quantifies the tendency of mu(+) to go in the proton direction and mu(-) to go in the antiproton direction. The results are consistent with the standard model and constrain new physics.